IMPACTS OF JELLYFISH: GELATINOUS PROBLEMS OR OPPORTUNITIES? Impactos de águas-vivas: problemas ou oportunidades gelatinosas? - Carrara Morandini, André (Arquivos de Ciências do Mar, 2022)
Some points related to the impacts (either negative or positive) caused by jellyfish(scyp homedusae) are briefly presented. Although medusae cause several negative impacts, they also have a positive side. It is argued that jellyfish blooms are becoming more frequent in areas where anthropogenic impacts are higher. Human perceptions of jellyfish need more study to better understand the role of these animals in the environment. Only then will we be able to decide if they are “good” or “bad”. Keywords: medusa, gelatinous zooplankton, Scyphozoa, marine zoology, marine impacts, climate change.